A substructure based method for damage assessment of RC frame structures under close-in explosion. (1st December 2022) - Shi, Yanchao; Jiang, Ren; Li, Zhong-Xian; Ding, Yang
Highlights: Methods to define the sub-structure range and its boundary conditions are proposed. A damage index for damage assessment of RC frame structure subjected to blast loads is defined based on energy conservation and could be derived through progressive collapse analysis of RC frames under close-in explosions. The substructure-based method for damage assessment of RC frame structure is proposed and proved to be accurate, reliable and more efficient as compared to conventional method. Abstract: Few studies are available in the literature on damage assessment of frame structures under blast loads although local damage of the structural components and even progressive collapse of building structures have been observed in terrorist or accidental explosions. In this paper, considering the initial damage of adjacent structural components under blast loading, a substructure based method for damage assessment of RC frame structures is proposed, including the proposal of the damage criterion, the principles for substructures selection and the calculation of the boundary conditions of the substructures. The accuracy and reliability of the proposed method are verified by comparing the results for damage assessment of a typical 5-story frame structure under different blast scenarios with the conventional method and the proposed method. The results indicated that the proposed method could rapidly and accurately predict the damage levels of the RC frame structure under a given blast load, especially when the building structures are damaged under close-in explosion.